Sоme aspects of attitude at patients with ulcer disease to physician’s recommendation - Ye. B. Anikina; A. M. Vavilov (Бюллетень сибирской медицины)
The рurpose of this work is the study of compliance of patients with peptic ulcer (PU). The results of the examination of 144 patients aging 18—82 with PU of different localization have been generalized.. The compliance of women with PU at all the phases of the disease was higher than that of men. The adequate attitude of patients to physician’s recommendations is a necessary condition for the improvement of treatment results.